PERMOHONAN PENINJAUAN KEMBALI AHLI WARIS TERPIDANA SECARA IN ABSENTIA DALAM PERKARA TINDAK PIDANA KORUPSI (Studi Kasus Putusan MA NOMOR 97 PK / PIDSUS / 2012) - Adi Purnomo Santoso (Jurnal Ilmu dan Budaya, 2018)
Judgment of Supreme Court Judicial Review (PK) Supreme Court (MA) Number 97 PK / PIDSUS / 2012 on 31 July 2013 chaired by Supreme Court Justice Suhadi and members of Sophian  Marthabaya, Andi Samsan Nganro, Sri Murwahyuni and Abdul Latief granted the Request for Judicial Review (PK) ) Wife of former Director of PT Bahana Pembinaan Usaha Indonesia (BPUI) Sudjiono Timan In Absentia for his actions which are considered to have cost the state USD $ 120 Million and Rp 98.7 Billion. With the verdict of the PK, it automatically canceled the decision of the Supreme Court Assembly declaring that Sudjiono Timan was guilty of dropping a sentence of 15 years in prison and a fine of Rp 50 million and paying the Rp 369 billion replacement money to Sudjiono Timan on December 3, 2004.